Pendidikan Aqil Baligh Dengan Pendekatan Psikologi Perkembangan Di MI Terpadu Mutiara - Rahmayanti Sormin, Mira; Tobroni, Tobroni; Faridi, Faridi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to determine the application of aqil puberty education using a developmental psychology approach at MI Terpadu Mutiara. This study used qualitative research methods. Data collection was carried out by observation, in-depth interviews, and documentation. Data that has been collected through data reduction, data presentation and drawing conclusions. The findings of this research are that aqil puberty education begins when students first enter school at MIT Mutiara. The approach to puberty aqil education in the MIT Mutiara school environment uses a developmental psychology approach starting from separating seating between male and female students. Implementation of aqil baligh education by adding aqil baligh material to the BPI (Islamic Personal Development) program. From BPI activities, teachers hope that students can have maturity in thinking and know the characteristics of the development they are experiencing so that they are able to overcome their personal problems related to the stages of physical and psychological development.